Searching for Sweetness : Women's Mobile lives in China and Lesotho - Hanisch, Sarah (Crossing seas (Hong Kong University Press), 2022)
Traversing from the rapidly urbanising county-level city of Fuqing to the remote mountainous kingdom of Lesotho in Southern Africa, 'Searching for Sweetness' is an extensive ethnography linking rural-to-urban migration in China with Chinese migration to Africa. Against the backdrop of China's national struggle for modernity and globalisation, Sarah Hanisch examines Chinese migrant women's complex and ever-shifting struggles for upward social mobility across different generations and localities in China and Lesotho.